The tadpole of Odontophrynus monachus Caramaschi & Napoli, 2012 (Amphibia, Anura: Odontophrynidae) - Menegucci, Rafael C.; Santos, Marcus Thadeu T.; Magalhães, Rafael F. De; Machado, Ibere F.; Garcia, Paulo C. A.; Pezzuti, Tiago L. (Zootaxa, 2016)
The genus Odontophrynus Reinhardt & Lütken comprises 11 species distributed throughout South and East of South America (Frost 2016) clustered in three phenetic groups: O. americanus, O. cultripes, and O. occidentalis (Savage & Cei 1965; Cei 1987; Caramaschi & Napoli 2012). Only the O. occidentalis group is recovered as monophyletic in the most recent phylogenetic hypotheses (Pyron & Wiens 2011; Pyron 2014). In these analyses, the O. cultripes group is not recovered and the monophyly of O. americanus group was not tested, since only one species of the group was included (Pyron & Wiens 2011; Pyron 2014). Therefore, the relationships within the genus are still inconclusive due to low support values and limited taxon sampling.